2003
DOI: 10.1021/ma020883+
|View full text |Cite
|
Sign up to set email alerts
|

Thiocarbonylthio Compounds (SC(Z)S−R) in Free Radical Polymerization with Reversible Addition-Fragmentation Chain Transfer (RAFT Polymerization). Effect of the Activating Group Z

Abstract: Free-radical polymerization in the presence of suitable addition-fragmentation chain transfer agents [SdC(Z)S-R] (RAFT agents) possess the characteristics of a living polymerization (i.e., polymer products can be reactivated for chain extension and/or block synthesis, molecular weights are predetermined by RAFT agent concentration and conversion, narrow polydispersities are possible). Styrene polymerizations (110 °C, thermal initiation) were performed for two series of RAFT agents [SdC(Z)S-CH 2Ph and SdC(Z)S-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
624
2
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 619 publications
(648 citation statements)
references
References 42 publications
(138 reference statements)
17
624
2
4
Order By: Relevance
“…In contrast, the value of C −tr,0 has a pronounced infl uence on the accuracy at which C tr,0 can be determined, as discussed further. It is clear from Table 4 that the accuracy of the method of Moad and co-workers [26][27][28] (Equation ( 8) 3,5,6). This is in line with expectations as the contribution of R 0 species reacting with macro-RAFT CTA will decrease accordingly and, hence, the underlying assumption for the derivation of Equation ( 8) will be more closely met.…”
Section: Methods To Determine C Tr0supporting
confidence: 77%
See 3 more Smart Citations
“…In contrast, the value of C −tr,0 has a pronounced infl uence on the accuracy at which C tr,0 can be determined, as discussed further. It is clear from Table 4 that the accuracy of the method of Moad and co-workers [26][27][28] (Equation ( 8) 3,5,6). This is in line with expectations as the contribution of R 0 species reacting with macro-RAFT CTA will decrease accordingly and, hence, the underlying assumption for the derivation of Equation ( 8) will be more closely met.…”
Section: Methods To Determine C Tr0supporting
confidence: 77%
“…[ 6,[10][11][12] Specifi cally for the RAFT polymerization process, Moad and co-workers developed an experimental method to directly determine C tr,0 based on the measured decay of the R 0 X concentration. [26][27][28] Assuming the PSSA for the concentration of the macroradicals and R 0 species they reported that…”
Section: Methods To Determine C (−)Tr0mentioning
confidence: 99%
See 2 more Smart Citations
“…Radical polymerization has significant advantages over ionic and coordination polymerization. The reaction conditions are usually less demanding and exhibit tolerance of trace impurities, and it is possible to polymerize a variety of monomers (Chiefari et al 2003).…”
Section: Polymer Graftingmentioning
confidence: 99%